Multiple Primary T-cell Lymphoma of the Colon and Ileum-Report of a Case - Yonemasu, Hirotoshi; Nagafuchi, Kazumitsu; Hirata, Shizuhiro; Yamasaki, Toru; Kishikawa, Hideki (Nippon Shokaki Geka Gakkai zasshi, 1998)
We report a case of multiple T-cell malignant lymphoma of the colon, and discussthis case in relation to the literature. An 89-year-old male was hospitalized with complaint of diarrhea. Barium enema and colonoscopy showed multiple ulcers ofthe rectum and sigmoid colon. Immunohistochemical stainings of biopsy specimens revealed T-cell malignant lymphoma. Emergency operation was performed because ofperforation of the sigmoid tumor. Resected specimen contained multiple ulcers ofthe colon and ileum. After the operation, the patient suffered from intractable, bloody and watery diarrhea. Anemia and hypoproteinemia could not be controlled and he died 71 days later. We speculate that remnant tumor might have existed. T-cell lymphoma of the colon is very rare, and only 16 cases have been reported inJapan. Its prognosis is much worse than that of of B-cell origin.